Understanding the link between child maltreatment and adolescent future expectations in Northern Uganda: A serial mediation analysis. (August 2020) - Saupe, Laura B.; Gößmann, Katharina; Catani, Claudia; Neuner, Frank
Abstract: Background: Recent research has identified high levels of child maltreatment and harsh parenting in post-war societies which have had detrimental effects on children's development. Future expectations are an important aspect of adolescents' development particularly in the challenging contexts of post-war societies where social instabilities and violence are prevalent. To date, however, the link between child maltreatment and adolescent future expectations remains understudied. Objective: By applying a socio-ecological perspective, this study aimed to investigate risk (internalizing symptoms) and protective factors (community integration) linking experiences of harsh parenting with adolescents' future expectations. Participants and Setting: Data was collected from N = 199 northern Ugandan adolescents (40.2 % females, Mage = 14.56 years) with structured interviews. Methods: Serial mediation analyses were calculated with child maltreatment as the predictor, future expectations as the outcome, and internalizing symptoms as well as community integration as mediating variables. Results: Results of the mediation model ( R 2 = .22, F (5193) = 10.54, p < .001, total effect ( b = -0.28, p < .005) revealed a direct effect of child maltreatment on future expectations (effect size: -.20, 95 % bootstrap CI = -0.40, -.01) as well as an indirect effect of child maltreatment via internalizing symptoms and community integration on future expectations (effect size of -.07 (95 % bootstrap CI = -0.14, -0.01). Conclusion: Child maltreatment was found to be linked to negative future expectations among Northern Ugandan adolescents, and both internalizing symptoms as well as community integration played mediating roles in the associations. Interventions should take psychopathology and community factors into account.